Marker-based Augmented Reality Application: "Easy Huayu" Mandarin for Beginners - Nurul Hafiza Mohd Pozi; Wan Shazlina Wan Ismail (Journal of Computing Technologies and Creative Content, 2022)
The Mandarin language is the second most spoken language globally as of 2021. In Malaysia, the motivation to learn Mandarin as an additional language is growing as most employers list "Fluent Mandarin speakers" as part of job requirements. Mobile application is one of the many ways to learn the Mandarin language. This research focuses on creating a marker-based Augmented Reality (AR) application, "Easy Huayu" that aims to educate the basics of Mandarin language to beginners and non-native speakers. The inclusion of AR and interactive multimedia elements in the study material will aid the users in memorizing the common phrases that can be used in day-to-day conversation. Besides that, this study also aims to analyze the effectiveness of interactive multimedia elements and AR as a tool to learn the Mandarin language. The researcher utilized the ADDIE model to approach this study, and Unity software was used to develop the application. At the end of this study, the researcher conducted an evaluation survey that returned positive feedback from the respondents. Based on the result, the users found the application to be effective in helping them learn the Mandarin language. Thus, fulfilling the objectives of this study.